Global Husaini; Identity Formation at Shrinescape - Syamsul Asri; Heddy Shry Ahimsa Putra; Albertus Bagus Laksana (UNHI PRESS, 2021)
Imam Husain`s martyrdom regains its global importance thanks to arbain walk, an annual inter-religious ziyarah event done by walking from Najaf to Karbala, along the route of which epic hospitality is being practiced for the comfort of Imam Husain`s devotee that coming from around the world. If Imam Husain`s martyrdom previously exist in revolutionary and spiritual imaginary of world leaders and mystics, arbain walk opens up a new path to convey Imam Husain`s legacy, in the sense that arbain walk reenact nonshi`i involvements in Karbala event thus make it as an arena for interreligious encounters. Those nonshi`i participated in 3 days walking from Najaf to Karbala are comprising of what I call global Husaini, emerge as the result of dynamic encounter in shrinescape of Imam Husain. Without this dynamics of shrinescape, global Husaini will be only a scattered presence of nonShi`is in communal pockets of Shi`i adherents around the world commemorating Imam Husain`s martyrdom.